1989
DOI: 10.1007/bf00114753
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrogen fertilization on the COS and CS2 emissions from temperature forest soils

Abstract: The net fluxes of carbonyl sulfide (COS) and carbon disulfide (CS2) to the atmosphere from nitrogen amended and unamended deciduous and coniferous forest soils were measured during the spring of 1986. We found that emissions of these gases from acidic forest soils were substantially increased after nitrogen fertilization. The total (COS + CS 2) emissions were increased by nearly a factor of three in the hardwood stand and were more than doubled in the pine stand. Furthermore, vegetation type appeared to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 32 publications
(27 reference statements)
5
19
1
Order By: Relevance
“…The enhanced OCS uptake rates by soils in the NITREX catchment may have been due to increased growth of plants and microorganisms which would be expected as a result of a greater N availability. This is in contrast to the findings of Melillo and Steudler [1989], who reported positive OCS fluxes (emissions) from soils in several forest plots, which increased by a factor of 3 following the addition of N fertilizer. They utilized a dynamic enclosure system with ambient air as the sweep gas.…”
Section: Effects Of Catchment Manipulations On Ocs Consumptioncontrasting
confidence: 99%
“…The enhanced OCS uptake rates by soils in the NITREX catchment may have been due to increased growth of plants and microorganisms which would be expected as a result of a greater N availability. This is in contrast to the findings of Melillo and Steudler [1989], who reported positive OCS fluxes (emissions) from soils in several forest plots, which increased by a factor of 3 following the addition of N fertilizer. They utilized a dynamic enclosure system with ambient air as the sweep gas.…”
Section: Effects Of Catchment Manipulations On Ocs Consumptioncontrasting
confidence: 99%
“…2a, 3 and 4) over a range of soil N concentrations between 0.38 and 10.2 g kg -1 (Table S1). Although this is the first study to demonstrate a significant relationship between soil N concentration and gross COS 5 production rates, previous studies have observed shifts in the magnitude of net COS and CS2 fluxes upon fertilisation with nitrate in both deciduous and evergreen coniferous forests (Melillo & Steudler, 1989). In addition a number of studies on agricultural soils in the US and China have observed large temperature-sensitive emissions of COS Liu et al, 2010;Maseyk et al, 2014;Whelan & Rhew, 2015).…”
Section: Drivers and Mechanisms Of Cos Production Across European Soimentioning
confidence: 64%
“…Fertilizer increases the production of S-containing AAs in wheat (43), and the metabolism or decomposition of these AAs may underlie increased COS emissions from fertilized soils (28,35,36,46). The SGP site was fertilized during the season as part of typical agricultural practice.…”
Section: Resultsmentioning
confidence: 99%
“…Soil COS emissions have also been observed and are usually associated with anoxic wetland soils (26,27), but production from forest soils (28) and from wheat, forest, and paddy soils at higher temperature (29) has been reported. Nonwetland soil emissions suggest either a COS-producing process operating under aerobic conditions or production from anoxic microsites distributed in the soil profile (30).…”
mentioning
confidence: 99%